Sericin in-situ reduced silver-loaded PET (Polyethylene Terephthalate) fiber as well as preparation method and application thereof

Through oxygen plasma treatment and sericin modification technology, silver ions are reduced in situ to silver nanoparticles, solving the problem of insufficient skin-friendliness and antibacterial properties of PET fibers, achieving efficient and long-lasting antibacterial effects and significant wetting and skin-friendliness.

CN119553490AActive Publication Date: 2025-03-04ANHUI AGRICULTURAL UNIVERSITY
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510109087.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-03-04
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

PET fibers have shortcomings in terms of skin-friendliness and antibacterial properties, resulting in limitations when used in certain applications, such as poor skin-friendliness, low hygroscopicity, and weak antibacterial properties.

Method used

The PET fibers are treated by oxygen plasma, and the carboxy groups on their surface are added, and then immersed in sericin solution for modification to form grafted modified PET fibers. Next, the grafted modified PET fibers were placed in a silver nitrate solution, and the silver ions were chelated on the surface of the PET fibers using sericin, and the silver ions were reduced to silver nanoparticles by in-situ reduction reaction.

Benefits of technology

The PET fiber is achieved with long-lasting and excellent antibacterial properties, significant wetting and skin-friendly properties, and the silver nanoparticles are uniformly and firmly combined on the fiber surface, improving the durability and washing resistance of the antibacterial effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553490A_ABST
    Figure CN119553490A_ABST
Patent Text Reader

Abstract

The invention discloses a sericin in-situ reduction silver-loaded PET fiber and a preparation method and application thereof, and belongs to the technical field of fiber materials.The preparation method of the sericin in-situ reduction silver-loaded PET fiber comprises the following steps that PET fiber is subjected to oxygen plasma treatment, and activated PET fiber rich in carboxyl groups is obtained; dipping the activated PET fiber in a sericin solution for modification to obtain a graft modified PET fiber; and placing the graft modified PET fiber in a silver nitrate solution, chelating silver ions on the surface of the PET fiber by using sericin, and reducing the silver ions into silver nanoparticles through an in-situ reduction reaction by using reductive amino acid contained in the PET fiber as a reducing agent to obtain the sericin in-situ reduced silver-loaded PET fiber. The sericin in-situ reduced silver-loaded PET fiber has the advantages of lasting and excellent antibacterial property, remarkable wettability and skin-friendly property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fiber materials, and in particular to a sericin in-situ reduced silver-loaded PET fiber and a preparation method and application thereof. Background Art

[0002] Polyethylene terephthalate (PET) fiber is a common synthetic fiber widely used in textiles, packaging materials and other fields. However, PET fiber has significant deficiencies in skin affinity and antibacterial properties, which limits its use in some applications. Due to the lack of polar groups such as carboxylic acid groups or hydroxyl groups in the PET molecular structure, its surface is highly hydrophobic and has low hygroscopicity, which leads to poor skin affinity of PET fiber. At the same time, this low hygroscopicity makes it impossible for PET fiber to effectively absorb and evaporate sweat when it comes into direct contact with the skin, causing the wearer to feel stuffy and uncomfortable. In addition, due to the poor air permeability of PET fiber, it is easy to form a hot and humid environment on the skin surface, providing favorable conditions for bacterial growth. People with sensitive skin are particularly susceptible to irritation and experience allergic reactions such as itching, redness and swelling. At the same time, the antibacterial properties of PET fiber are relatively weak. Although the antibacterial properties of PET fibers can be improved by physical or chemical modification methods, there are many problems. For example, by adding antibacterial agents to the surface, these methods are often costly and have limited durability. The surface coating method has weak binding force, and the antibacterial durability needs to be improved. Although the physical mixing method is simple, the selection and addition of antibacterial components are limited. Excessive antibacterial components will affect the intrinsic mechanical properties of the fiber, which leads to unsatisfactory antibacterial effects of the fiber. In addition, the physical mixing method usually requires high temperature and a long blending process. PET may degrade during high-temperature processing, affecting its antibacterial properties.

[0003] As a new type of antibacterial agent, silver nanoparticles are widely used in the preparation of antibacterial materials due to their unique physical and chemical properties, such as high specific surface area, high electron affinity and good biocompatibility. In the field of PET antibacterial, the introduction of silver nanoparticles can significantly improve the antibacterial properties of the material, thus playing an important role in the fields of medical treatment, food packaging and textiles. At present, most of the reported studies directly blend silver nanoparticles with PET or graft them onto the surface of PET fibers after modification. However, the high activity and nano-size effect of silver nanoparticles will cause them to easily agglomerate and cannot be evenly dispersed on the surface and inside of PET, thus affecting the antibacterial properties of the fiber. At the same time, the antibacterial PET obtained by blending, coating or physical adsorption may cause silver poisoning due to the loose binding of silver nanoparticles, which will cause adverse effects on human health and nature. Therefore, in order to solve the problems of easy agglomeration and poor binding of silver nanoparticles when compounded with PET, as well as poor skin affinity of PET fibers, it is urgent to develop a new method for preparing PET fiber materials with both skin affinity and long-lasting antibacterial properties. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing silver-loaded PET fibers by in-situ reduction of sericin to solve the problems raised in the above-mentioned background technology.

[0005] To achieve the above objectives, the embodiments of the present invention provide the following technical solutions: A method for preparing sericin in-situ reduced silver-loaded PET fiber, comprising the following steps: The PET fibers are treated with oxygen plasma to obtain activated PET fibers rich in carboxyl groups; The activated PET fiber is immersed in a sericin solution for modification to obtain a grafted modified PET fiber; The grafted modified PET fiber is placed in a silver nitrate solution, the silver ions are chelated on the surface of the PET fiber using sericin, and the reducing amino acids contained in it are used as reducing agents to reduce the silver ions into silver nanoparticles through an in situ reduction reaction to obtain sericin in situ reduced silver-loaded PET fiber.

[0006] Preferably, the power of the oxygen plasma treatment is 10-300 W, and the time is 5-60 min.

[0007] Preferably, the step of immersing the activated PET fiber in a sericin solution for modification to obtain the grafted modified PET fiber specifically comprises: The activated PET fiber is immersed in a sericin solution, and a composite catalyst is used to catalyze a cross-linking reaction so that the activated PET fiber and the sericin are firmly bonded to form an amide covalent bond to obtain a grafted modified PET fiber; the composite catalyst is a composite system of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide; the mass ratio of the 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide to N-hydroxysuccinimide is (1.8-2.2):1.

[0008] Preferably, the sericin solution is an ethanol-water solution of sericin; the mass concentration of sericin in the ethanol-water solution is 1%-10%; the ethanol-water solution consists of anhydrous ethanol and deionized water, and the volume ratio of anhydrous ethanol to deionized water is (8.5-9.5):(0.5-1.5).

[0009] Preferably, the pH value of the reaction system for the catalytic cross-linking reaction is 3-6, the reaction temperature is 1-10° C., and the reaction time is 24-72 h.

[0010] Preferably, the mass volume ratio of the activated PET fiber to the sericin solution is 1 kg:(30-100) L.

[0011] Preferably, the silver nitrate solution is an aqueous solution of silver nitrate, and its concentration is 50-100 mmol / L.

[0012] Preferably, the mass volume ratio of the grafted modified PET fiber to the silver nitrate solution is 1 kg:(30-100) L.

[0013] Another object of the present invention is to provide a sericin in-situ reduced silver-loaded PET fiber prepared by the above-mentioned preparation method, wherein the silver nanoparticles in the sericin in-situ reduced silver-loaded PET fiber are loaded on the surface of the grafted modified PET fiber through coordination chelation; and the grafted modified PET fiber is a PET fiber to which sericin is bonded through amide covalent bonds.

[0014] Another object of the present invention is to provide a use of the above-mentioned sericin in-situ reduced silver-loaded PET fiber in the preparation of an antibacterial agent.

[0015] The invention provides a method for preparing silver-loaded PET fiber by in-situ reduction of sericin. The method comprises treating PET with oxygen plasma to obtain activated PET fiber rich in oxygen-containing active groups such as carboxyl groups, and improving the surface roughness and wettability of the fiber. Then, the activated PET fiber is used as a carrier, and microcavities and concave holes on its surface are used as anchor points. The sericin is modified on the surface of the PET fiber by a composite catalyst to obtain a grafted modified PET fiber covalently cross-linked with sericin. The sericin combines the silver ions in the silver nitrate solution with the PET fiber by coordination chelation, and the silver ions are in-situ reduced to silver nanoparticles by reducing amino acids such as tyrosine, aspartic acid and glutamic acid contained in the sericin as reducing agents. The oxygen plasma activated PET fiber has a large number of oxygen-containing polar groups such as carboxyl groups and hydroxyl groups. The sericin is firmly combined with the activated PET through amide covalent bonds, and the three-dimensional porous structure is used for chelation fixation and green in-situ reduction to synthesize silver nanoparticles. The preparation method provided by the invention is green and environmentally friendly, and the prepared sericin in-situ reduced silver-loaded PET fiber has durable and excellent antibacterial properties, significant wettability and skin affinity. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Scanning electron micrographs of activated PET fibers treated with oxygen plasma; in the figure, (a). Scanning electron micrograph of PET fibers before modification; (b). Scanning electron micrograph of PET fibers treated with oxygen plasma.

[0017] Figure 2 These are scanning electron micrographs of silver-loaded PET fibers reduced by in situ reduction of sericin; in the figure, (a) is a scanning electron micrograph of silver-loaded PET fibers reduced by in situ reduction of sericin at a magnification of 5000 times; (b) is a scanning electron micrograph of silver-loaded PET fibers reduced by in situ reduction of sericin at a magnification of 10000 times.

[0018] Figure 3 This is the XRD pattern of silver-loaded PET fiber in situ reduced with sericin.

[0019] Figure 4 Element distribution diagram of silver-loaded PET fiber after in-situ reduction of sericin; in the figure, (a). Surface scanning electron microscope image of element analysis of silver-loaded PET fiber after in-situ reduction of sericin; (b). Element content distribution diagram of silver-loaded PET fiber after in-situ reduction of sericin; (c). Distribution diagram of elements contained in silver-loaded PET fiber after in-situ reduction of sericin.

[0020] Figure 5 This is the infrared spectrum of the silver-loaded PET fiber in situ reduced with sericin.

[0021] Figure 6These are qualitative test diagrams of the antibacterial activity of silver-loaded PET fibers subjected to in-situ reduction of sericin; in the figure, (a) is a test diagram of the antibacterial activity of PET fibers before modification against Staphylococcus aureus; (b) is a test diagram of the antibacterial activity of silver-loaded PET fibers subjected to in-situ reduction of sericin against Staphylococcus aureus.

[0022] Figure 7 This is the moisture regain diagram of silver-loaded PET fiber reduced by in-situ sericin. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0024] In one embodiment of the present invention, a method for preparing silver-loaded PET fibers by in-situ reduction of sericin is provided, which comprises the following steps: S1, treating the PET fiber with oxygen plasma to obtain activated PET fiber rich in carboxyl groups; S2, immersing the activated PET fiber in a sericin solution for modification to obtain a grafted modified PET fiber; S3. The grafted modified PET fiber is placed in a silver nitrate solution, the silver ions are chelated on the surface of the PET fiber using sericin, and the reducing amino acids contained in the sericin are used as reducing agents to reduce the silver ions into silver nanoparticles through an in-situ reduction reaction, thereby obtaining sericin in-situ reduced silver-loaded PET fiber.

[0025] In the sericin in-situ reduced silver-loaded PET fiber prepared in the embodiment of the present invention, the silver nanoparticles are loaded on the surface of the grafted modified PET fiber through coordination chelation; the grafted modified PET fiber is a PET fiber to which sericin is bonded through amide covalent bonds.

[0026] In a preferred embodiment of the present invention, the power of the oxygen plasma treatment is 10-300 W, and the time is 5-60 min.

[0027] In a preferred embodiment of the present invention, the step of immersing the activated PET fiber in a sericin solution for modification to obtain the grafted modified PET fiber specifically comprises: The activated PET fiber is immersed in a sericin solution, and a composite catalyst is used to catalyze a cross-linking reaction so that the activated PET fiber and the sericin are firmly bonded to form an amide covalent bond to obtain a grafted modified PET fiber; the composite catalyst is a composite system of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide; the mass ratio of the 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide to N-hydroxysuccinimide is (1.8-2.2):1, preferably 2:1.

[0028] In a preferred embodiment of the present invention, the sericin solution is an ethanol-water solution of sericin; the mass concentration of sericin in the ethanol-water solution is 1%-10%; the ethanol-water solution consists of anhydrous ethanol and deionized water, and the volume ratio of anhydrous ethanol to deionized water is (8.5-9.5):(0.5-1.5), preferably 9:1.

[0029] In a preferred embodiment of the present invention, the pH value of the reaction system of the catalytic cross-linking reaction is 3-6, the reaction temperature is 1-10° C., and the reaction time is 24-72 h.

[0030] In a preferred embodiment of the present invention, the mass volume ratio (bath ratio) of the activated PET fiber to the sericin solution is 1 kg:(30-100)L.

[0031] In a preferred embodiment of the present invention, the silver nitrate solution is an aqueous solution of silver nitrate with a concentration of 50-100 mmol / L.

[0032] In a preferred embodiment of the present invention, the mass volume ratio (bath ratio) of the grafted modified PET fiber to the silver nitrate solution is 1 kg: (30-100) L.

[0033] In another embodiment of the present invention, there is also provided an application of the above-mentioned sericin in-situ reduction silver-loaded PET fiber in the field of antibacterial; as a reducing agent and dispersant, sericin reduces the silver ions on the surface of the PET fiber into silver nanoparticles in-situ, and binds to the surface of the PET fiber through coordination chelation, which enables the silver nanoparticles to be evenly and firmly bound to the surface of the PET fiber, and the PET fiber has a lasting antibacterial property. At the same time, sericin has excellent skin affinity and hygroscopicity, giving the PET fiber efficient and excellent antibacterial properties, significant wettability and skin affinity. The sericin in-situ reduction silver-loaded PET fiber has an excellent and long-lasting antibacterial effect and excellent antibacterial washability.

[0034] Specifically, the technical solution provided by the embodiment of the present invention has the following beneficial effects: (1) Activated PET fibers were obtained by oxygen plasma treatment, which improved the surface roughness and wettability of the fibers. Sericin was firmly bonded to the activated PET through amide covalent bonds. The natural affinity and three-dimensional structure of sericin provided a stable carrier for silver nanoparticles, which not only helped to prevent the aggregation of metal particles, but also improved the efficiency of catalytic reduction. Finally, with the help of reducing amino acids such as tyrosine, aspartic acid and glutamic acid contained in sericin as reducing agents, the silver ions on the surface of the PET fibers were reduced in situ into silver nanoparticles. At the same time, sericin has excellent skin affinity and hygroscopicity, which endows PET fibers with high efficiency, excellent antibacterial properties, significant wettability and skin affinity.

[0035] (2) As a reducing agent and dispersant, sericin reduces the silver ions on the surface of PET fibers into silver nanoparticles in situ and binds to the surface of PET fibers through coordination chelation. This enables the silver nanoparticles to be evenly and firmly bound to the surface of PET fibers, and PET fibers have long-lasting antibacterial properties.

[0036] (3) The in-situ reduction silver-loaded PET fiber of sericin prepared in the embodiment of the present invention can be used in the antibacterial field, and the synthesis technology of the silver-containing antibacterial agent in the PET fiber is green and environmentally friendly. The in-situ reduction silver-loaded PET fiber of sericin has excellent and long-lasting antibacterial effect and excellent antibacterial and washable properties, and has great application prospects in the field of functional antibacterial textiles.

[0037] The following embodiments are some specific implementation cases of the present invention in practical applications, but are not limited thereto.

[0038] Example 1: This example provides a method for preparing silver-loaded PET fibers by in-situ reduction of sericin, which comprises the following steps: S1, treating the PET fiber with oxygen plasma at a power of 100 W for 15 min to obtain activated PET fiber rich in carboxyl groups; S2, the activated PET fiber obtained above is immersed in an ethanol aqueous solution of sericin with a mass concentration of 5% at a bath ratio of 1kg:50L, the ethanol aqueous solution is composed of anhydrous ethanol and deionized water at a volume ratio of 9:1, and a composite catalyst composed of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide at a mass ratio of 2:1 is added to react, and the activated PET fiber and the sericin are firmly bonded to form an amide covalent bond through a catalytic cross-linking reaction to obtain a grafted modified PET fiber; during the reaction, the pH value of the reaction system is adjusted by using morpholineethanesulfonic acid monohydrate, the pH value of the reaction system for the catalytic cross-linking reaction is 5, the reaction temperature is 4°C, and the reaction time is 24 h; S3. The grafted modified PET fiber is placed in an aqueous solution of 80 mmol / L silver nitrate at a bath ratio of 1kg:90L for reaction. The silver ions are chelated on the surface of the PET fiber using sericin, and the reducing amino acids contained in it are used as reducing agents. The pH value of the solution is adjusted by sodium hydroxide. The reaction conditions are pH=9, the reaction temperature is 70°C, and the reaction time is 5 h. The silver ions are reduced into silver nanoparticles through an in-situ reduction reaction to obtain sericin in-situ reduced silver-loaded PET fiber.

[0039] Example 2: This example provides a method for preparing silver-loaded PET fibers by in-situ reduction of sericin, which comprises the following steps: S1, treating the PET fiber with oxygen plasma at a power of 200 W for 10 min to obtain activated PET fiber rich in carboxyl groups; S2, the activated PET fiber obtained above is immersed in an ethanol aqueous solution of sericin with a mass concentration of 8% at a bath ratio of 1kg:70L, the ethanol aqueous solution is composed of anhydrous ethanol and deionized water at a volume ratio of 9:1, and a composite catalyst composed of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide at a mass ratio of 2:1 is added to react, and the activated PET fiber and the sericin are firmly bonded to form an amide covalent bond through a catalytic cross-linking reaction to obtain a grafted modified PET fiber; during the reaction, the pH value of the reaction system is adjusted by using morpholineethanesulfonic acid monohydrate, the pH value of the reaction system for the catalytic cross-linking reaction is 3, the reaction temperature is 9°C, and the reaction time is 36 h; S3. The grafted modified PET fiber is placed in a 60 mmol / L silver nitrate aqueous solution at a bath ratio of 1kg:60L for reaction. The silver ions are chelated on the surface of the PET fiber using sericin, and the reducing amino acids contained in it are used as reducing agents. The pH value of the solution is adjusted by sodium hydroxide. The reaction conditions are pH=8, reaction temperature is 80°C, and reaction time is 8 h. The silver ions are reduced into silver nanoparticles through an in-situ reduction reaction to obtain sericin in-situ reduced silver-loaded PET fiber.

[0040] Example 3: This example provides a method for preparing silver-loaded PET fibers by in-situ reduction of sericin, which comprises the following steps: S1, treating the PET fiber with oxygen plasma at a power of 300 W for 5 min to obtain activated PET fiber rich in carboxyl groups; S2, immersing the activated PET fiber obtained above in an ethanol aqueous solution of sericin with a mass concentration of 10% at a bath ratio of 1kg:100L, wherein the ethanol aqueous solution is composed of anhydrous ethanol and deionized water in a volume ratio of 9:1, and adding a composite catalyst composed of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide in a mass ratio of 2:1 to react, so that the activated PET fiber and the sericin are firmly bonded to form an amide covalent bond through a catalytic cross-linking reaction, thereby obtaining a grafted modified PET fiber; during the reaction, the pH value of the reaction system is adjusted by using morpholineethanesulfonic acid monohydrate, and the pH value of the reaction system for the catalytic cross-linking reaction is 6, the reaction temperature is 10°C, and the reaction time is 72 h; S3. The grafted modified PET fiber is placed in a 100 mmol / L silver nitrate aqueous solution at a bath ratio of 1kg:100L for reaction. The silver ions are chelated on the surface of the PET fiber using sericin, and the reducing amino acids contained in it are used as reducing agents. The pH value of the solution is adjusted by sodium hydroxide. The reaction conditions are pH=12, reaction temperature is 60°C, and reaction time is 10h. The silver ions are reduced into silver nanoparticles through an in-situ reduction reaction to obtain sericin in-situ reduced silver-loaded PET fiber.

[0041] Example 4: This example provides a method for preparing silver-loaded PET fibers by in-situ reduction of sericin, which comprises the following steps: S1, treating the PET fiber with oxygen plasma at a power of 10 W for 60 min to obtain activated PET fiber rich in carboxyl groups; S2, immersing the activated PET fiber obtained above in an ethanol aqueous solution of sericin with a mass concentration of 3% at a bath ratio of 1kg:(50-100)L, wherein the ethanol aqueous solution is composed of anhydrous ethanol and deionized water in a volume ratio of 9:1, and adding a composite catalyst composed of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide in a mass ratio of 2:1 to react, so that the activated PET fiber and the sericin are firmly bonded to form an amide covalent bond through a catalytic cross-linking reaction, thereby obtaining a grafted modified PET fiber; during the reaction, the pH value of the reaction system is adjusted by using morpholineethanesulfonic acid monohydrate, the pH value of the reaction system for the catalytic cross-linking reaction is 3, the reaction temperature is 2°C, and the reaction time is 70 h; S3. The grafted modified PET fiber is placed in a 90 mmol / L silver nitrate aqueous solution at a bath ratio of 1kg:70L for reaction. The silver ions are chelated on the surface of the PET fiber using sericin, and the reducing amino acids contained in it are used as reducing agents. The pH value of the solution is adjusted by sodium hydroxide. The reaction conditions are pH=11, reaction temperature is 65°C, and reaction time is 9 h. The silver ions are reduced into silver nanoparticles through an in-situ reduction reaction to obtain sericin in-situ reduced silver-loaded PET fiber.

[0042] Example 5: This example provides a method for preparing silver-loaded PET fibers by in-situ reduction of sericin, which comprises the following steps: S1, treating the PET fiber with oxygen plasma at a power of 150 W for 50 min to obtain activated PET fiber rich in carboxyl groups; S2, the activated PET fiber obtained above is immersed in an ethanol aqueous solution of sericin with a mass concentration of 7% according to a bath ratio of 1kg:80L, the ethanol aqueous solution is composed of anhydrous ethanol and deionized water in a volume ratio of 9:1, and a composite catalyst composed of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide in a mass ratio of 2:1 is added to react, and the activated PET fiber and the sericin are firmly bonded to form an amide covalent bond through a catalytic cross-linking reaction to obtain a grafted modified PET fiber; during the reaction, the pH value of the reaction system is adjusted by using morpholineethanesulfonic acid monohydrate, the pH value of the reaction system for the catalytic cross-linking reaction is 5, the reaction temperature is 7°C, and the reaction time is 30 h; S3. The grafted modified PET fiber is placed in a 75 mmol / L silver nitrate aqueous solution at a bath ratio of 1kg:30L for reaction. The silver ions are chelated on the surface of the PET fiber using sericin, and the reducing amino acids contained in it are used as reducing agents. The pH value of the solution is adjusted by sodium hydroxide. The reaction conditions are pH=12, reaction temperature is 75°C, and reaction time is 8.5 h. The silver ions are reduced into silver nanoparticles through an in-situ reduction reaction to obtain sericin in-situ reduced silver-loaded PET fiber.

[0043] Example 6: This example provides a method for preparing silver-loaded PET fibers by in-situ reduction of sericin, which comprises the following steps: S1, treating the PET fiber with oxygen plasma at a power of 90 W for 52 min to obtain activated PET fiber rich in carboxyl groups; S2, the activated PET fiber obtained above is immersed in an ethanol aqueous solution of sericin with a mass concentration of 7.2=5% at a bath ratio of 1kg:30L, the ethanol aqueous solution is composed of anhydrous ethanol and deionized water in a volume ratio of 9:1, and a composite catalyst composed of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide in a mass ratio of 2:1 is added to react, and the activated PET fiber and the sericin are firmly bonded to form an amide covalent bond through a catalytic cross-linking reaction to obtain a grafted modified PET fiber; during the reaction, the pH value of the reaction system is adjusted by using morpholineethanesulfonic acid monohydrate, the pH value of the reaction system for the catalytic cross-linking reaction is 4, the reaction temperature is 7°C, and the reaction time is 24 h; S3. The grafted modified PET fiber is placed in a 95 mmol / L silver nitrate aqueous solution at a bath ratio of 1kg:85L for reaction. The silver ions are chelated on the surface of the PET fiber using sericin, and the reducing amino acids contained in it are used as reducing agents. The pH value of the solution is adjusted by sodium hydroxide. The reaction conditions are pH=10, reaction temperature is 64°C, and reaction time is 9.5 h. The silver ions are reduced into silver nanoparticles through an in-situ reduction reaction to obtain sericin in-situ reduced silver-loaded PET fiber.

[0044] Example 7: This example provides a method for preparing silver-loaded PET fibers by in-situ reduction of sericin, which comprises the following steps: S1, treating the PET fiber with oxygen plasma at a power of 10 W for 60 min to obtain activated PET fiber rich in carboxyl groups; S2, the activated PET fiber obtained above is immersed in an ethanol aqueous solution of sericin with a mass concentration of 1% according to a bath ratio of 1kg:50L, the ethanol aqueous solution is composed of anhydrous ethanol and deionized water in a volume ratio of 8.5:1.5, and a composite catalyst composed of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide in a mass ratio of 1.8:1 is added to react, and the activated PET fiber and the sericin are firmly bonded to form an amide covalent bond through a catalytic cross-linking reaction to obtain a grafted modified PET fiber; during the reaction, the pH value of the reaction system is adjusted by using morpholineethanesulfonic acid monohydrate, the pH value of the reaction system for the catalytic cross-linking reaction is 3, the reaction temperature is 1°C, and the reaction time is 24 h; S3. The grafted modified PET fiber is placed in a 50 mmol / L silver nitrate aqueous solution at a bath ratio of 1kg:50L for reaction. The silver ions are chelated on the surface of the PET fiber using sericin, and the reducing amino acids contained in it are used as reducing agents. The pH value of the solution is adjusted by sodium hydroxide. The reaction conditions are pH=9, reaction temperature is 70°C, and reaction time is 5 h. The silver ions are reduced into silver nanoparticles through an in-situ reduction reaction to obtain sericin in-situ reduced silver-loaded PET fiber.

[0045] Example 8: This example provides a method for preparing silver-loaded PET fibers by in-situ reduction of sericin, which comprises the following steps: S1, treating the PET fiber with oxygen plasma at a power of 300 W for 5 min to obtain activated PET fiber rich in carboxyl groups; S2, the activated PET fiber obtained above is immersed in an ethanol aqueous solution of sericin with a mass concentration of 10% according to a bath ratio of 1kg:100L, the ethanol aqueous solution is composed of anhydrous ethanol and deionized water in a volume ratio of 9.5:0.5, and a composite catalyst composed of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide in a mass ratio of 2.2:1 is added to react, and the activated PET fiber and the sericin are firmly bonded to form an amide covalent bond through a catalytic cross-linking reaction to obtain a grafted modified PET fiber; during the reaction, the pH value of the reaction system is adjusted by using morpholineethanesulfonic acid monohydrate, the pH value of the reaction system for the catalytic cross-linking reaction is 6, the reaction temperature is 10°C, and the reaction time is 72 h; S3. The grafted modified PET fiber is placed in a 100 mmol / L silver nitrate aqueous solution at a bath ratio of 1kg:100L for reaction. The silver ions are chelated on the surface of the PET fiber using sericin, and the reducing amino acids contained in it are used as reducing agents. The pH value of the solution is adjusted by sodium hydroxide. The reaction conditions are pH=9, reaction temperature is 70°C, and reaction time is 5 h. The silver ions are reduced into silver nanoparticles through an in-situ reduction reaction to obtain sericin in-situ reduced silver-loaded PET fiber.

[0046] Performance test: Taking the sericin in-situ reduced silver-loaded PET fiber prepared in Example 1 as an example, relevant performance research and analysis were carried out. The results are as follows: Figure 1-Figure 7 And as shown in Table 1.

[0047] in, Figure 1 Scanning electron micrograph of activated PET fibers treated with oxygen plasma. Figure 1 As can be seen from (a), the surface of the untreated PET fiber sample is relatively smooth; Figure 1(b) shows that after plasma treatment, obvious concave holes and microcavities appeared on the surface of polyester fiber, and the surface roughness increased significantly. This change is attributed to the impact of high-energy particles in the plasma, including the etching effect caused by the bombardment of positive and negative ions and neutral particles. In this process, the macromolecular chemical bonds on the fiber surface are destroyed, and then react with free radicals in the plasma to generate oxygen-containing groups, thereby changing the chemical properties and morphological characteristics of the fiber surface. In order to confirm the successful synthesis of sericin in-situ reduction silver-loaded PET fiber, the microscopic morphology of the fiber was analyzed using a scanning electron microscope.

[0048] Figure 2 This is a scanning electron microscope image of the in-situ reduction of sericin-loaded silver-loaded PET fiber. Figure 2 (a) and (b) are scanning electron microscope images at different magnifications. Sericin is firmly bonded to activated PET through amide covalent bonds. The natural affinity and three-dimensional structure of sericin provide a stable carrier for silver nanoparticles, which not only helps to prevent the aggregation of metal particles, but also improves the efficiency of catalytic reduction. Finally, with the help of reducing amino acids such as tyrosine, aspartic acid and glutamic acid contained in sericin as reducing agents, the silver ions on the surface of PET fibers are in situ reduced to silver nanoparticles. The silver nanoparticles have regular morphology and uniform size. At the same time, it can be seen that the silver nanoparticles are evenly and firmly bonded to the surface of PET fibers. This is mainly because the coordination chelation of oxygen-containing groups in sericin with Ag + Combined with sericin, as a reducing agent and dispersant, it can reduce the silver ions on the surface of PET fibers into silver nanoparticles in situ, and bind to the surface of PET fibers through coordination chelation, which enables the silver nanoparticles to be evenly and firmly bound to the surface of PET fibers, providing a basis for the high-performance and long-lasting antibacterial properties of PET fibers.

[0049] In order to confirm the existence of silver nanoparticles, the crystal types of PET fibers before modification and PET fibers loaded with silver after in-situ reduction of sericin were analyzed by X-ray diffractometer. Figure 3 As shown. The XRD spectrum of the PET fiber before modification was analyzed and it was found that the broad peak at 2θ=22.09° belonged to the original PET fiber. After the PET fiber was modified with AgNPs, four diffraction peaks were observed at 2θ=34.76°, 44.17°, 65.53°, and 77.07° in the XRD spectrum, corresponding to the (111), (200), (220), and (311) reflections of the metallic silver fcc structure, respectively. Therefore, it can be clearly seen that the silver nanoparticles on the surface of the PET fiber are crystalline.

[0050] In order to demonstrate that silver nanoparticles are uniformly and firmly loaded on the PET surface, the distribution and content of the elements in the fiber were analyzed using an element spectrometer. The results are as follows: Figure 4 shown. Figure 4 This is the element distribution map of silver-loaded PET fiber in situ reduced with sericin. Figure 4 (a) is a surface scanning electron micrograph of the elemental analysis of the silver-loaded PET fiber after in-situ reduction of sericin. It can be seen from the figure that the silver nanoparticles are uniformly and firmly loaded on the surface of the PET fiber. Figure 4 (b) is the element content distribution diagram of the fiber. It can be seen from the figure that the Ag content can reach 16 Wt%, which indicates that the sericin in situ reduced silver-loaded PET fiber contains a large amount of silver nanoparticles, which also provides a theoretical basis for the antibacterial property of the fiber. Figure 4 (c) is the distribution diagram of the elements contained in the silver-loaded PET fiber after in-situ reduction of sericin. It can be seen from the figure that the silver nanoparticles are evenly distributed on the surface of the PET fiber. This is attributed to the chelation coordination and in-situ reduction of sericin. As a dispersant and reducing agent, sericin can chelate the Ag uniformly on the surface of the PET fiber. + It was reduced to silver nanoparticles and firmly bound to the surface of PET fibers, which further confirmed that the method of preparing silver-loaded PET fibers by in situ reduction of sericin can solve the problem of poor dispersion of antibacterial silver nanoparticles on the PET surface.

[0051] In order to further confirm that the in-situ reduction reaction occurred on the surface of PET fiber, the chemical structure changes of PET fiber before and after modification were characterized by infrared spectroscopy. The results are as follows: Figure 5 shown. Figure 5 This is the infrared spectrum of the silver-loaded PET fiber in situ reduced with sericin. It can be seen from the figure that the infrared spectrum of polyethylene terephthalate fiber (PET fiber) has the following characteristic absorption bands: 1709 cm -1 The carbonyl (C=O) stretching vibration at 1240 cm -1 and 1088 cm -1 The COC stretching vibration at 1240 cm -1 and 1088 cm -1 The two strong absorption peaks with similar intensities at 700-900 cm -1 There are abundant absorption peaks in the range of 718 cm -1 The absorption peak at 865 cm is attributed to the out-of-plane bending vibration of the hydrogen atom on the para-disubstituted benzene ring. Although it is not very typical, it can still be used as one of the evidences for the existence of terephthalic acid groups. -1 The absorption peak at ~2920 cm is attributed to the out-of-plane bending vibration of two adjacent CH bonds on the aromatic ring. -1The absorption peak of 1450-1620 cm -1 There should also be multiple absorption peaks related to the vibration of the benzene ring skeleton in the interval, but due to the high symmetry of the molecule, the intensity of these absorption peaks is weak and not significant enough. Figure 5 It can be seen that sericin molecules have a wavelength of 1585, 1505 cm and 1405 cm -1 The absorption peaks near represent the absorption bands of amide I, amide II, and amide III, respectively. Amide I is mainly caused by the stretching vibration of the C=O group, indicating that there is a β-turn structure in sericin. The absorption band of amide II represents the NH bending and CN stretching vibrations. At the same time, the generation of amide III is caused by the combination of CN stretching vibration and in-plane NH bending vibration, which indicates that there is a large amount of random curl in the secondary structure of sericin. In addition, sericin has a large number of random curls at 1505 and 1075 cm -1 The absorption peaks at 3057 cm-1 are caused by the bending vibration of CH and -OH in the sericin side chain and the stretching vibration of CC. -1 There is an obvious single peak at , which is the characteristic absorption peak formed by the superposition of NH stretching vibration and OH stretching vibration. Figure 5 It can be seen that no new signal peaks appear in the molecular structure of PET fibers after oxygen plasma treatment, indicating that oxygen plasma treatment does not destroy the PET macromolecular chain structure, and retains the complete structure and excellent physical and chemical properties of PET. The following reactions can occur in PET fibers treated with oxygen plasma: RH→R·+H· R·+O2→ROO· ROO·+R1H→ROOH+R1· R·+O·→RO· The reaction shows that the C-C bonds in the PET molecules are destroyed during the plasma treatment and then recombined with oxygen atoms to generate oxygen-containing polar groups. Therefore, oxygen plasma treatment can not only increase the roughness of the fiber surface, but also introduce hydrophilic polar groups such as hydroxyl, carboxyl, and aldehyde groups on the surface of PET fibers, thereby significantly improving the hydrophilicity of PET fibers. This surface modification provides favorable conditions for the subsequent plasma grafting of sericin.

[0052] It is worth noting that the silver-loaded PET fiber has a -1Obvious carbonyl (C=O) stretching vibrations appeared, and the intensity was significantly higher than that of PET fibers treated with oxygen plasma. This indicates that the carboxyl groups (COOH) on the surface of PET fibers obtained by oxygen plasma reacted with the free amino groups in sericin under the catalysis of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide / N-hydroxysuccinimide, and the carbonyl (C=O) in the amide bond increased significantly by 1710 cm -1 The peak intensity at 1565 cm-1 indicates that the reaction process is mainly that 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide first reacts with the free carboxyl groups on the PET surface to form an amino-reactive O-acylurea intermediate. This intermediate reacts with the amino groups in sericin to form a bond of the two compounds through an amide bond. However, this intermediate is very unstable in aqueous solution and is easily hydrolyzed. By adding N-hydroxysuccinimide, this intermediate can be converted into an amino-reactive N-hydroxysuccinimide ester, thereby greatly improving the efficiency of the condensation reaction mediated by 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide. At the same time, at 1565 cm-1, the peak intensity at 1565 cm-1 indicates ... -1 、1500cm -1 、1408cm -1 At 1565 cm-1, the absorption peak signals of amide I, amide II and amide III appeared, but the peak intensities of the three places decreased significantly. This is because the amidation between PET and sericin molecules treated with oxygen plasma reduced the number of corresponding primary amino groups and increased amide bonds by the cross-linking mechanism catalyzed by 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide / N-hydroxysuccinimide. The Fourier transform infrared spectrum of the silver-loaded PET fiber after catalytic cross-linking mainly showed a decrease in the ratio of the peak intensities of amide I, amide II and amide III, i.e., the peaks at 1565 cm-1 decreased significantly. -1 1500cm-cm -1 1408cm -1 The changes in the intensity of these absorption peaks further confirmed that the oxygen plasma-treated PET and sericin molecules underwent cross-linking reactions through catalysis. -1 It can be seen that the -OH stretching vibration peak appears on the PET surface, which indicates that the hydrophilicity of the silver-loaded PET fiber is significantly improved after the sericin grafting, which will be conducive to the expansion of the application field of silver-loaded PET. These cross-linked sericins can act as chelating agents to bind Ag in the AgNO3 solution. +Through coordination, sericin is firmly bound to the surface of PET fibers. At the same time, sericin also has natural affinity and three-dimensional structure, which provides a stable carrier for metal nanoparticles. This structure not only helps to prevent the aggregation of metal particles, but also improves the efficiency of catalytic reduction. Finally, the tyrosine, aspartic acid and glutamic acid rich in sericin have reducing ability. As a reducing agent, it can chelate Ag on the surface of PET fibers. + In situ reduction to silver nanoparticles, which are firmly bound to the surface of PET fibers.

[0053] Figure 6 This is a qualitative test chart of the antibacterial property of silver-loaded PET fiber reduced by in situ sericin. Figure 6 (a) is the antibacterial test diagram of PET fiber before modification against Staphylococcus aureus. It can be seen that no inhibition zone appears, which indicates that the unmodified PET fiber does not have antibacterial properties. Figure 6 (b) is the antibacterial picture of the modified PET fiber, and an obvious inhibition zone can be seen, indicating that the in situ reduced silver-loaded PET fiber of sericin has excellent antibacterial properties against Staphylococcus aureus, which is attributed to the efficient bactericidal effect of the silver nanoparticle antibacterial agent on the surface of the PET fiber.

[0054] Table 1 is a quantitative analysis of the antibacterial activity of the in-situ reduction of sericin-loaded silver-loaded PET fiber against Staphylococcus aureus and Escherichia coli. S. aureus and Escherichia coli, E. coli ) to simulate and verify the antibacterial performance of the in-situ reduction of sericin silver-loaded PET fiber in practical applications. To facilitate the operation of the antibacterial experiment, the aerogel was compressed into sheets before the test. According to GB / T20944.3-2008 Evaluation of Antibacterial Properties of Textiles Part 3: Oscillation Method, the sericin in-situ reduction silver-loaded PET fiber samples were cut into pieces and placed in a flask, and then 70 mL of phosphate buffer (PBS, pH ≈ 7.2) and 5 ml of bacterial solution (3×10 5 -4×10 5cfu / mL), and then the flask was shaken at 24°C for 18h; 1mL of culture solution was taken out, diluted and evenly dispersed on an agar plate, incubated at 37°C for 24-48h, and the number of colonies grown was counted. The antibacterial rate was calculated by the formula, and the results are shown in Table 1 (the units of each data in Table 1 are %). As can be seen from Table 1, the unmodified PET fiber has basically no antibacterial effect on Staphylococcus aureus and Escherichia coli, which is attributed to the stability and chemical inertness of the structure. The antibacterial effects of PET fiber before modification on Staphylococcus aureus and Escherichia coli were 2.14% and 1.47%, respectively, and the antibacterial rates after 30 washes were 0.92% and 0.43%, respectively. The antibacterial effects of sericin in situ reduced silver-loaded PET fiber on Staphylococcus aureus and Escherichia coli were 99.95% and 97.38%, respectively, which is mainly because silver nanoparticles release silver ions (Ag) when they come into contact with bacteria. + ), these silver ions can directly destroy the cell membrane structure of bacteria, leading to the rupture of the cell membrane and the leakage of contents, thereby inhibiting the growth and reproduction of bacteria. At the same time, silver nanoparticles can induce bacteria to produce a large number of reactive oxygen species (ROS). These free radicals will attack the cell components of bacteria, such as proteins, DNA and lipids, thereby interfering with the normal metabolism and physiological functions of bacteria. Silver nanoparticles can penetrate the cell membrane of bacteria, causing changes in the permeability of the cell membrane, causing the outflow of substances in the cell, and ultimately leading to the death of bacteria. At the same time, it can be seen that after 30 washes, the antibacterial rates of the sericin in situ reduced silver-loaded PET fiber against Staphylococcus aureus and Escherichia coli still reached 90% and 85% respectively, which shows that its antibacterial effect is long-lasting, and the sericin in situ reduced silver-loaded PET fiber has antibacterial washing resistance. In summary, the difference in antibacterial effects verifies the antibacterial effect of the sericin in situ reduced silver-loaded PET fiber, which also provides theoretical support and potential for the sericin in situ reduced silver-loaded PET fiber in real antibacterial applications.

[0055] Table 1

[0056] Figure 7 The figure is the moisture regain of silver-loaded PET fiber in situ reduced with sericin. PET is treated with oxygen plasma to obtain activated PET fiber rich in oxygen-containing active groups such as carboxyl groups, while improving the surface roughness and wettability of the fiber. Furthermore, sericin is firmly grafted on the surface of PET fiber through covalent bonding, so that PET fiber has the biocompatibility, skin affinity and functionality of sericin. Figure 7 As shown, compared with the official moisture regain of 0.4% of recycled PET, the moisture regain of the fiber prepared by this technology reaches 2.5%, which is more than 6 times higher than that of natural cotton fiber. The hydrophilicity is significantly improved, and the silver-loaded PET fiber loaded with sericin in situ reduction has excellent skin-friendliness and wettability.

[0057] Based on the above-mentioned ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above-mentioned description. The technical scope of the present invention is not limited to the contents of the specification.

Claims

1. A method for preparing silver-loaded PET fiber by in-situ reduction of sericin, characterized in that: The following steps are involved: The PET fibers are treated with oxygen plasma to obtain activated PET fibers rich in carboxyl groups; The activated PET fiber is immersed in a sericin solution for modification to obtain a grafted modified PET fiber; The grafted modified PET fiber is placed in a silver nitrate solution, the silver ions are chelated on the surface of the PET fiber using sericin, and the reducing amino acids contained in it are used as reducing agents to reduce the silver ions into silver nanoparticles through an in situ reduction reaction to obtain sericin in situ reduced silver-loaded PET fiber.

2. The method for preparing silver-loaded PET fiber by in-situ reduction of sericin according to claim 1, characterized in that: The power of oxygen plasma treatment is 10-300 W, and the time is 5-60 min.

3. The method for preparing silver-loaded PET fiber by in-situ reduction of sericin according to claim 1, characterized in that: The step of immersing the activated PET fiber in a sericin solution for modification to obtain the grafted modified PET fiber specifically comprises: The activated PET fiber is immersed in a sericin solution, and a composite catalyst is used to catalyze a cross-linking reaction so that the activated PET fiber and the sericin are firmly bonded to form an amide covalent bond to obtain a grafted modified PET fiber; the composite catalyst is a composite system of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide; the mass ratio of the 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide to N-hydroxysuccinimide is (1.8-2.2):

1.

4. The method for preparing silver-loaded PET fiber by in-situ reduction of sericin according to claim 1 or 3, characterized in that: The sericin solution is an ethanol-water solution of sericin; the mass concentration of sericin in the ethanol-water solution is 1%-10%; the ethanol-water solution is composed of anhydrous ethanol and deionized water, and the volume ratio of anhydrous ethanol to deionized water is (8.5-9.5):(0.5-1.5).

5. The method for preparing silver-loaded PET fiber by in-situ reduction of sericin according to claim 3, characterized in that: The pH value of the reaction system for the catalytic cross-linking reaction is 3-6, the reaction temperature is 1-10°C, and the reaction time is 24-72 h.

6. The method for preparing silver-loaded PET fiber by in-situ reduction of sericin according to claim 1, characterized in that: The mass volume ratio of the activated PET fiber to the sericin solution is 1kg:(30-100)L.

7. The method for preparing silver-loaded PET fiber by in-situ reduction of sericin according to claim 1, characterized in that: The silver nitrate solution is an aqueous solution of silver nitrate, and its concentration is 50-100 mmol / L.

8. The method for preparing silver-loaded PET fiber by in-situ reduction of sericin according to claim 1 or 7, characterized in that: The mass volume ratio of the grafted modified PET fiber to the silver nitrate solution is 1kg:(30-100)L.

9. A silver-loaded PET fiber obtained by in-situ reduction of sericin using the preparation method according to any one of claims 1 to 8, characterized in that: The silver nanoparticles in the sericin in-situ reduced silver-loaded PET fiber are loaded on the surface of the grafted modified PET fiber through coordination chelation; the grafted modified PET fiber is a PET fiber bonded with sericin through amide covalent bonds.

10. Use of the sericin in-situ reduced silver-loaded PET fiber as claimed in claim 9 in the preparation of an antibacterial agent.

Citation Information

Patent Citations

  • Preparation method of nano silver-protein composite aqueous solution and protein-modified nano silver antibacterial textiles

    CN103628314A

  • Preparation method of natural sericin grafted modified regenerated PET fiber

    CN113756095A

  • Simple and efficient aged silk fibroin protein fiber repairing method

    CN113846485A

  • Process for composite modification of hyaluronic acid and carboxymethyl cellulose

    CN1837265A

  • Mesoporous zirconium-phosphate loaded nano-silver antibacterial polyester fiber and method for preparation thereof

    WO2017092234A1